Titanium carbide and carbide-derived carbon composite nanofibers by electrospinning of Ti-resin precursor - Martin, Jan R.; Borchardt, Lars; Oschatz, Martin; Mondin, Giovanni; Kaskel, Stefan (Chemie Ingenieur Technik, 2013)
TiO2/C and TiC/C composite nanofibers were produced by electrospinning of resin/TiCl4 precursor solution. The resulting ceramic fiber webs were porous and showed surface areas as high as 523 m 2g-1. They were further converted to carbide-derived carbon (CDC) fibers under full retention of the fiber-like shape and flexibility. These CDC membranes showed a hierarchical pore structure and specific surface as high as 1378 m2g-1. Applications in the area of high temperature filtration, catalyst support and energy storage are conceivable. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbide-derived carbons; Composite fibers; Electrospinning; Phenol formaldehyde resin; Titanium carbide